Post-discharge major bleeding, myocardial infarction and mortality risk after coronary artery bypass grafting: a nationwide cohort study from the SWEDEHEART registry. (14th October 2021) - Bjoerklund, E; Nielsen, S J; Tygesen, H; Martinsson, A; Hansson, E C; Lindgren, M; Malm, C J; Pivodic, A; Jeppsson, A
Abstract: Background: Platelet inhibition and occasionally oral anticoagulants are used after coronary artery bypass grafting (CABG) to reduce ischaemic events but may increase bleeding risk. The impact of post-discharge major bleeding and myocardial infarction on mortality risk in CABG patients is unknown. Methods: All patients who underwent first-time isolated CABG in Sweden 2006–2017 and survived 14 days after discharge were included. Individual patient data from five mandatory national registries (SWEDEHEART, National Patient Register, Swedish Prescribed Drug Register, Cause of Death Register and The Swedish Population Register) were merged. Post-discharge major bleeding and myocardial infarction were defined as hospitalization with a bleeding or myocardial infarction diagnosis as main diagnosis respectively. A Cox proportional piecewise hazard model for the effect of time-updated bleeding and myocardial infarction as first post-discharge event on subsequent mortality risk was developed. The model was adjusted for age, sex, year of surgery, comorbidities at baseline and time-updated use of platelet inhibitors, oral anticoagulants and other secondary prevention medications. To estimate the time-dependent risk on mortality after an event, hazard ratios were calculated for <30 days, 30–365 days and >365 days after first incidence of major bleeding and myocardial infarction. Results: In total 36 633 patients were included and median follow-up was 6.0 years (25th-75th percentile 3.0–9.0 years). During follow-up, 2265 (6.2%) patients suffered a major bleeding and 2108 (5.8%) patients a myocardial infarction as a first post-discharge event. In total 6683 (18.2%) died during follow-up. Both major bleeding and myocardial infarction were significantly associated with increased mortality risk compared to patients without any major bleeding or myocardial infarction. The adjusted hazard ratios for mortality <30 days after major bleeding were 21.45 (95% CI 18.27–25.20) and 22.00 (95% CI 18.29–26.45) after myocardial infarction, 4.04 (95% CI 3.57–4.56) and 4.54 (95% CI 3.88–5.31) 30–365 days after the event and 1.57 (95% CI 1.43–1.72) and 2.07 (95% CI 1.86–2.30) >365 days after the event, all compared to patients without major bleeding or myocardial infarction. Conclusion: Major bleeding and myocardial infarction as first post-discharge event after CABG had similar incidence and were associated with a significant and comparable increase in mortality risk. The risk was highest during the first 30 days after the event. Strategies to prevent myocardial infarction and major bleeding events after CABG are of great importance to improve survival. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Heart-Lung FoundationSparbanken Sjuhärads stiftelse för forskning vid Södra Älvsborgs Sjukhus